Multianalytical approach in the study of the composition and functionality of the microbiota associated with carbon and nitrogen cycles in soils under preserved and disturbed environments - Chaves, Miriam Gonçalves de (2020)
The implementation of different agricultural management practices and land use systems promote physicochemical changes in soil associated with loss of nitrogen (N) and carbon (C) from soil and greenhouse gases (GHG) emission. In Brazil, the expansion of sugarcane production and land use changes can affect microbial groups that play essential roles in biogeochemical cycles of N and C. This thesis focused on the microbial community structure, composition, and functions associated with the N and C cycling on sugarcane-cultivated soil and soils under different land use in the Brazilian Amazon. Using a culture-independent approach based on high-throughput DNA sequencing and microarray technology, this thesis is composed by three chapters: the first and the second chapters encompass studies applying GeoChip v.5.0M microarray technology to investigate N and C functional genes as potential bioindicators of vinasse organic residue in combination with N mineral fertilizer in archaeal and acidobacterial communities inhabiting sugarcane-cultivated soil. In the third chapter, the co-occurrence of archaeal taxonomic groups was evaluated in primary and secondary forests, agricultural and cattle pasture soils in the Brazilian Amazon based on high-throughput amplicon sequencing and qPCR of the 16S rRNA gene. Our results in sugarcane-cultivated soil revealed that 87% of genes families associated with N metabolism from soil microbiota were responsive to vinasse with N fertilizer in 7 first days after application. The main gene families responsives were related to processes of nitrification (amoA and hao), ammonification (gdh and ureC), and denitrification (p450nor). The potential O2 decrease and the increase of K and P due vinasse addition can promote the growth of halophile Archaea (Natronomonas) and N2O reducing bacteria (Anaeromyxobacter), but also decrease ammonia oxidizer bacteria (AOB). Regarding the Acidobacteria, subgroups Gp13 and Gp18 revealed positive correlations with the C gene families associated with degradation, especially hemicellulose, but low abundance in vinasse presence. On the other hand, Gp4 was the most abundant acidobacterial subgroup in the vinasse treatment but was not associated with C gene families. This soil management practice can reduce the total Acidobacteria abundance, including that potentially involved with C degradation in sugarcane crops. The co-occurrence of archaeal classes analysis revealed that forest to pasture or agriculture conversion in Amazonian may reduce the syntropy between groups, an important strategy from Archaea to get energy and can promote the reduction of key groups related to N metabolism as ammonia oxidizer Archaea (AOA). These findings of the microbial functionality associated with N and C cycle in tropical soils can support public policy to mitigate N losses in sustainable agroecosystems